2005
DOI: 10.1002/ejlt.200401112
|View full text |Cite
|
Sign up to set email alerts
|

Formation and decomposition of stigmasterol hydroperoxides and secondary oxidation products during thermo‐oxidation

Abstract: The oxidation mechanisms of stigmasterol at 100 and 180 7C were investigated by using the HPLC-UV-FL method. An overall picture of the oxidation status was achieved with a single HPLC analysis, enabling us to monitor the formation and decomposition of both primary and secondary oxidation products. The oxidation behavior of stigmasterol was different at the two temperatures. At 180 7C, the amounts of hydroperoxides increased sharply during the first 10 min and then began to decrease. At 100 7C, the amounts of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…The total amount of polar oxidation products accounted thus only for 18% of the initial stigmasterol indicating that other types of products had to be formed. The polar oxides may have been suffered further reactions, such as polymerization (Kemmo, Soupas, Lampi & Piironen, 2005;Soupas et al, 2006) or dehydration, giving rise to other types of non polar products (Bortolomeazzi, De Zan, Pizzale & Lanfranco, 2000). These results are in agreement with those obtained by Lampi, Juntunen, Toivo and Piironen (2002), with a maximum content of polar oxidation products after 1 hour heating of stigmaterol at 180 ºC 7-ketostigmasterol was the only product whose content increased statistically during the whole course of the experiment.…”
Section: Effects Of Thermo-oxidation On Stigmasterol As Measured By Psupporting
confidence: 87%
“…The total amount of polar oxidation products accounted thus only for 18% of the initial stigmasterol indicating that other types of products had to be formed. The polar oxides may have been suffered further reactions, such as polymerization (Kemmo, Soupas, Lampi & Piironen, 2005;Soupas et al, 2006) or dehydration, giving rise to other types of non polar products (Bortolomeazzi, De Zan, Pizzale & Lanfranco, 2000). These results are in agreement with those obtained by Lampi, Juntunen, Toivo and Piironen (2002), with a maximum content of polar oxidation products after 1 hour heating of stigmaterol at 180 ºC 7-ketostigmasterol was the only product whose content increased statistically during the whole course of the experiment.…”
Section: Effects Of Thermo-oxidation On Stigmasterol As Measured By Psupporting
confidence: 87%
“…In this sense, Soupas et al (35) proposed 140 °C as the key temperature in the process, since sterols behaved differently below and above this temperature. At 175-180 °C, whereas Xu et al (30) found the maximum amount of COPs at similar times as in our experiment, some other works, (14,32,36) obtained that SOPs decreased only after 40, 60 and 90 min, respectively.…”
Section: Effect Of Heating Treatmentsupporting
confidence: 82%
“…Besides, instead of the ones we analyzed, other oxides could have been formed, such as 6-hydroxy, 20-hydroxy, 22-hydroxy, dienes, trienes… (29,36,63). Moreover, SOPs derived from cholesterol and stigmasterol could have decomposed to form oligomers, polymers and other compounds characteristic of advanced stages of oxidation (29,39), yielding an overall lower balance than for campesterol and sitosterol derived oxides.…”
Section: Effect Of the Type Of Sterolmentioning
confidence: 95%
“…Thus, it was concluded that 7-keto derivatives represent a simple, reliable marker of the extent of PS oxidation in food (Cercaci et al 2007). Although the distribution of POP may depend on the oxidation phase/status as well (Kemmo et al 2005), the 7-keto derivatives were the most abundant oxides.…”
Section: Impact Of Frying On the Total Amount Of Psmentioning
confidence: 98%